(untitled) (Swiss Medical Weekly, 2025)
Switzerland’s Electronic Patient Record (EPR) system faces a critical adoption crisis: less than 2% of the population has opened an account despite years of investment. To understand this failure from the citizen’s perspective, we launched the first “expedition” in which 120 volunteers (“salutonauts”) systematically tested Switzerland’s current digital health infrastructure by opening EPRs, requesting their health data and documenting their experiences. This represents the first real-world, citizen-led assessment of Switzerland’s health data infrastructure. Our findings reveal three fundamental insights. First, citizens appreciate the concept of personally controlled health records governed by a trustworthy national framework. Second, the current EPR implementation is both impractical and economically untenable under existing conditions: opening an EPR nationwide would cost CHF 400 million (calculated from required man-hours alone), while uploading historic documents would cost CHF 1 billion, and obtaining insurance claims data would cost over CHF 5 billion in lost productivity. Third, the recently announced draft of the new Electronic Health Dossier Law (E-GD) comes at a critical moment, since evidence-based redesign of the EPR system is essential. 95% of participants valued comprehensive medical checkups producing structured data, demonstrating citizens’ appetite for high-quality digital health records when they provide tangible benefits. Our expedition methodology, which is agile, citizen-centred and involves real-world testing, offers a replicable model for evaluating digital health initiatives before massive implementation costs are incurred. With the E-GD revision underway, Switzerland has a unique opportunity to develop an EPR system that serves patients and physicians above all. Successful implementation requires EPR opening at birth by default (with the ability to opt-out), the AI-powered automation of data collection and uploading, seamless healthcare professional interfaces, and using the EPR as the billing data gateway. The alternative – i.e. continuing the current approach – virtually guarantees failure based on economic factors alone.